The effects of major events on the volatility of currency exchange rate: an empirical evidence of the European market - Fu, Jiayi (2019)
This paper investigates on the effects of two major events, namely the Brexit and the US-China trade war on the return and volatility of the pound against the dollar (GBP/USD), the euro against the dollar (EUR/USD) and the euro against the franc (EUR/CHF), and also the effects of critical dates during the events on the selected pairs’ return and volatility.